Evaluation of Radish (Raphanus sativus L.) Varieties under Shade-net Condition for Yield and Quality - Dahal, Kumar Mani; Bhattarai, Dhruba Raj; Sharma, Moha Dutta; Poudel, Bishwash (Nepalese Horticulture, 2021)
This experiment was carried out in a shade net house at the horticultural research farm of Agriculture and Forestry University, Chitwan, Nepal during spring 2018 to identify the suitable radish (Raphanus sativus L.) variety having high yield potential with better quality roots for off season. The experiment was laid out in Randomized Complete Block Design (RCBD) with eight treatments, i.e. five improved (Vedetar Local, Miyasinge, Tokinasi, Pusa Chetki and All Season) and three hybrid varieties (Mino Early Long White F1, Ivory White F1 and MAHY 22 F1) of radish with four replications. Radish seeds were seeded in the third week of February. Miyasinge variety showed the highest plant height (43.91 cm), biomass yield (73.22 t ha-1) and fresh shoot weight per plant (127.15 g) whereas the highest number of leaves per plant (20.54) was recorded in MAHY 22 F1. Ivory White F1 variety showed the highest root length (19.51 cm), root circumference (9.31 cm), root to shoot ratio per plant (1.29) and fresh root yield (30.87 t ha-1). The highest root skin thickness (0.27 cm) was found in Miyasinge, the highest TSS (6.20 ºBrix) was observed in Mino Early Long White F1. Ivory White F1 showed the highest ascorbic acid content (19.51 mg 100 g-1), dry matter of root (7.62 %) and score (8.36) from the consumers’ acceptability test for pungency. Ivory White F1 showed superior growth, yield and quality attributes under shed net conditions.